Is Economic Growth Good for the Poor? Tracking Low Incomes Using General Means - James E. Foster; Miguel Székely (Inter-American Development Bank, Research Department, 2001)
In this paper we propose the use of an alternative methodology to track low incomes based on Atkinson`s (1970) family of equally distributed equivalent income functions, which are called general means here. We provide a new characterization of general means that justifies their use in this context. Our method of evaluating the effects of growth on poor incomes is based on a comparison of growth rates for two standards of living: the ordinary mean and a bottom-sensitive general mean. The motivating question is: To what extent is growth in the ordinary mean accompanied by growth in the general mean? A key indicator in this approach is the growth elasticity of the general mean, or the percentage change in the general mean over the percentage change in the usual mean. Our empirical analysis estimates this growth elasticity for a data set containing 144 household surveys from 20 countries over the last quarter century. Among other results, we find that the growth elasticity of bottom sensitive general means is positive, but significantly smaller than one. This suggests that the incomes of the poor do not grow one-for-one with increases in average income.
Keywords: 330; Wirtschaftswachstum; Armut; Lebensstandard; Niedrigeinkommen; Schätzung; Lateinamerika; USA; Südostasien